Methods of test for sodium tripolyphosphate (pentasodium triphosphate) and sodium pyrophosphate (tetrasodium pyrophosphate) for industrial use. Determination of particle size distribution Part 5, (7th June 1974) - British Standards Institution,
No abstract available